ANALYSIS OF THE MEANING OF KHASYYATULLAH IN THE SUFI-FORMED QUR'AN - Azmi Zarkasyi; Faisal Setiawan Fajri (Sean Institute, 2022)
Analysis of the literature and language of the Qur'an is important and needed in studying the Qur'an, because between them is an important point in understanding it. Islam is a source of guidance that teaches its adherents to always fear Allah in the joints of their lives. However, not a few Muslims have this attitude, other than for reasons their hearts are unsure and turn away from Allah, and because they do not know Allah. This paper examines the verses related to the Khasyatullah in the Al-Qur'an. The analysis was carried out using a Sufistic approach based on the book of commentaries by Ibn Arabi al-Qusyairi, Al-Alusi, al-Tustari, Said Hawwa and Hamka. In the Sufistic view, the meaning of Khasyatullah is the fear of Allah which is possessed by people who have high faith so that it will require them to always fear Allah. Al-Qur'an specializes the owner of this Khasyatullah to scholars, namely people who know the greatness and power of Allah. With the Khasyatullah, a person will always renew repentance, restrain lust, do good deeds, establish social ties, and turn the mosque into a prosperous place that is very much filled by Muslims. Therefore, efforts to create a harmonious society to always be close to and fear Allah can only be achieved through collective sufism.